A wear-resistant and durable one-way isolation material and its preparation method and application

By using unidirectional isolation materials with modified acrylate copolymers and nanomagnesium silicate, the problem of resin penetration in the existing isolation film in the vacuum infusion molding process is solved, and higher wear resistance, durability and moisture permeability are achieved.

CN118978842BActive Publication Date: 2025-03-25ZHEJIANG YOUWEI NEW MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410980054.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-03-25
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing isolation films are prone to resin penetration in the vacuum infusion molding process, resulting in the scrapping of vacuum exhaust equipment, and the polyurethane resin is poorly durable when used as a primer affinity layer, affecting the isolation performance.

Method used

A unidirectional isolation material with modified acrylate copolymer as the main film-forming raw material is used. By adding modified nanomagnesium silicate, hydrated magnesium silicate and titanium dioxide, medium-soft self-crosslinking emulsions are prepared to improve the wear resistance, durability and moisture permeability of the material.

Benefits of technology

The service life of one-way isolation materials has been extended, and its isolation performance and wear resistance in the vacuum infusion molding process of wind power blades has been improved, thereby avoiding the problem of resin penetration.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of preparation of insulating materials, and specifically discloses a wear-resistant and durable one-way insulating material and a preparation method and application thereof, wherein the one-way insulating material comprises the following raw materials in parts by weight: 60 to 80 parts of modified acrylate copolymer, 2 to 8 parts of modified nano magnesium silicate, 10 to 20 parts of hydrated magnesium silicate, 1 to 3 parts of titanium dioxide, 0.01 to 0.05 parts of defoaming agent and 0.01 to 0.03 parts of leveling agent; wherein the viscosity of the modified acrylate copolymer is 1000 to 2000 mPa·s at 25°C. The one-way insulating material provided by the present invention is a one-way insulating material with acrylate polymer as the main raw material, excellent wear resistance and durability, and not easy to be damaged, which significantly extends the service life of the one-way insulating material, and has excellent performance when used in the vacuum infusion molding process of wind turbine blades as a one-way insulating membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of insulating materials, and specifically discloses a wear-resistant and durable one-way insulating material and a preparation method and application thereof. Background Art

[0002] The vacuum infusion molding process includes the vacuum resin introduction process and the wet vacuum bag molding process. The main principle is to use a vacuum pump to keep the molding cavity in a negative pressure state, and use the negative pressure difference to pour the molding resin into the cavity. In the fields of aerospace and wind turbine blades, due to the large size of the products and the long vacuum infusion process time, the performance and applicability of the vacuum auxiliary materials in the molding process are also increasingly required. The vacuum auxiliary materials commonly mentioned in the prior art include vacuum bag film, isolation film, breathable felt, sealing tape, pressure-sensitive tape, release cloth and guide net.

[0003] The isolation film is a one-way breathable film, which is a material that can block resin and allow gas to pass through. It is composed of a release cloth and a semi-permeable membrane. When the performance of the isolation film is poor, it is very easy for the resin to enter the vacuum pumping equipment through the vacuum pumping pipe during the continuous glue pouring process, causing the vacuum pumping equipment to be scrapped.

[0004] The utility model patent with patent application number 202022342408.0 discloses a breathable isolation membrane, comprising a substrate layer (1) and a coating (4), wherein a waterproof layer (2) and a primer affinity layer (3) are provided between the substrate layer (1) and the coating (4), and the primer affinity layer (3) is a polyurethane coating, which improves the moisture permeability, air permeability and cold resistance of the product, and has good air permeability while blocking the resin, and is softer and more comfortable to the touch; adding the primer affinity layer can increase the surface tension of the substrate, thereby allowing the substrate and the adhesive to bond together better and not easily delaminated. However, when polyurethane resin is used as the primer affinity layer, poor durability is prone to occur, and the viscosity of the polyurethane resin may also have an adverse effect on the air permeability of the isolation membrane.

[0005] In view of this, there is an urgent need for a wear-resistant and durable one-way isolation material to solve the shortcomings and defects of existing isolation membranes. Summary of the invention

[0006] In view of the defects of the prior art, the present invention provides a wear-resistant and durable one-way insulation material and its preparation method and application. The one-way insulation material provided by the present invention is a one-way insulation material with an acrylic polymer as the main film-forming raw material, excellent in wear resistance and durability, and not prone to damage. The service life of the one-way insulation material is extended, and the one-way insulation material has excellent performance when used in the vacuum infusion molding process of wind turbine blades as a one-way insulation membrane.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On one hand, the present invention provides a wear-resistant and durable one-way insulating material, which comprises the following raw materials in parts by weight: 60 to 80 parts of a modified acrylic copolymer, 2 to 8 parts of modified nano magnesium silicate, 10 to 20 parts of hydrated magnesium silicate, 1 to 3 parts of titanium dioxide, 0.01 to 0.05 parts of a defoaming agent, and 0.01 to 0.03 parts of a leveling agent;

[0009] Wherein, the viscosity of the modified acrylate copolymer is 1000-2000 mPa·s at 25°C.

[0010] In some embodiments of the present invention, the preparation steps of the modified acrylate copolymer are as follows:

[0011] (1) adding an emulsifier and deionized water into a container to obtain an emulsifier solution;

[0012] (2) Add the emulsifier solution obtained in step (1) into the reactor, then add the fluorine-containing monomer, nano-silica, vinyl acetate, butyl acrylate, hydroxyethyl methacrylate and catalyst in sequence, disperse by ultrasound for 30 to 40 minutes, heat to 50 to 60° C., react for 20 to 30 minutes, add the first part by weight of initiator, keep the temperature for reaction for 30 to 40 minutes, add the second part by weight of initiator within 2 to 3 hours, wait for the temperature to drop to 20 to 30° C. after the reaction is completed, and filter to obtain the modified polyacrylate.

[0013] In some embodiments of the present invention, the mass ratio of vinyl acetate to butyl acrylate is 1:(1-2).

[0014] Preferably, the mass ratio of vinyl acetate to butyl acrylate is 1:1.5.

[0015] In some embodiments of the present invention, the amount of the fluorine-containing monomer added is 1 to 5% of the total mass of vinyl acetate and butyl acrylate.

[0016] Preferably, the amount of the fluorine-containing monomer added is 3% of the total mass of vinyl acetate and butyl acrylate.

[0017] Preferably, the fluorine-containing monomer is dodecafluoroheptyl methacrylate.

[0018] Preferably, the amount of hydroxyethyl methacrylate added is 1-3% of the total mass of vinyl acetate and butyl acrylate.

[0019] Preferably, the added amount of the nano-silicon dioxide is 1 to 1.5% of the total mass of vinyl acetate, butyl acrylate, hydroxyethyl methacrylate and fluorine-containing monomer.

[0020] Preferably, the emulsifier is fatty alcohol polyoxyethylene ether.

[0021] More preferably, the EO number of the fatty alcohol polyoxyethylene ether is 9.

[0022] Preferably, the amount of the emulsifier added is 2-4% of the total mass of vinyl acetate and butyl acrylate.

[0023] Preferably, the catalyst is sodium hydroxide, and the added amount is 0.5-1% of the total mass of vinyl acetate and butyl acrylate.

[0024] Preferably, the initiator is ammonium persulfate, and the added amount is 0.5-1.2% of the total mass of vinyl acetate and butyl acrylate.

[0025] The invention prepares a medium-soft self-crosslinking emulsion by copolymerizing vinyl acetate, butyl acrylate and hydroxyethyl methacrylate monomers, and modifying them with fluorine-containing organic monomers and nano-silicon dioxide. By controlling the copolymerization amount of vinyl acetate, butyl acrylate and hydroxyethyl methacrylate, the elasticity and ductility of the copolymer are improved, and it is not easy to be damaged. At the same time, the stability is stronger, and the usability is improved. Under a specific monomer copolymerization amount, the hydroxyethyl methacrylate monomer avoids the adverse effect on the moisture permeability caused by the condensation of part of the hydroxyl groups at high temperature to form ether bonds and then form a film on the surface of the substrate cloth. When the abundant hydrophilic groups such as hydroxyl groups are attached to the substrate cloth, the moisture permeability of the isolation material is significantly improved. The organic fluorine methacrylate dodecafluoroheptyl is specifically selected to modify the acrylate copolymer, which may be due to the F element having It has the characteristics of strong electronegativity and low surface tension. When it is coated on the substrate cloth, the F-containing segments gather in the outer layer, which greatly reduces the surface tension of the substrate cloth, and the protective effect of the formed CF bonds effectively improves the durability of the substrate cloth; the applicant also adds nano-silicon dioxide to participate in the polymerization of the acrylate copolymer. The addition of nano-silicon dioxide particles improves the durability and stability of the copolymer. The uniform distribution of the particles increases the uniformity of the performance of the modified acrylate copolymer, and when it is used as a coating resin film for polyester or nylon substrate cloth, it has good wash fastness and extends the service life of the unidirectional isolation material; on the other hand, the unidirectional isolation material with modified acrylate copolymer and composite magnesium silicate filler as the main raw materials can form a continuous microporous structure on the surface of the substrate cloth, and exert good unidirectional isolation performance.

[0026] In some embodiments of the present invention, the preparation steps of the modified nano magnesium silicate are as follows:

[0027] Add nano magnesium silicate and a modifier into a reactor, mix and stir at a speed of 2000-2500 r / min for 2-10 minutes to obtain the modified nano magnesium silicate.

[0028] In some embodiments of the present invention, the modifier is a mixture of a titanate coupling agent and paraffin wax.

[0029] Preferably, the titanate coupling agent is titanate coupling agent LK-201.

[0030] Preferably, the mass ratio of the titanate coupling agent to paraffin is 1:(0.1-0.5).

[0031] Further preferably, the mass ratio of the titanate coupling agent to the paraffin is 1:0.3.

[0032] In some embodiments of the present invention, the amount of the modifier added is 1-5% of the mass of the nano-magnesium silicate.

[0033] Preferably, the amount of the modifier added is 3% of the mass of the nano-magnesium silicate.

[0034] The applicant modified the nano magnesium silicate by adding a specific titanate coupling agent and paraffin wax, and realized the organic coating of the nano magnesium silicate and the bonding effect of the paraffin wax by coupling, thereby increasing the compatibility and stability of the nano magnesium silicate in the system. At the same time, by utilizing its small size and high chemical reactivity, it is deposited on the micro defects of the friction surface of the one-way isolation material, which can better fill the friction interface and improve the wear resistance of the one-way isolation material to increase the service life. On the other hand, the chemical stability of the modified nano magnesium silicate is improved. When it is compatible with other components in the system, it can also effectively improve the chemical resistance and scrub resistance of the one-way isolation material.

[0035] At the same time, the applicant also found that the tensile strength of the unidirectional isolation material was improved to a certain extent after the addition of modified nano-magnesium silicate. The possible reason is that the nano-silica particles in the modified acrylate copolymer and the modified nano-magnesium silicate played a synergistic effect between the nano-particles. Both have small particle sizes and low melting points, which improves the ductility of the unidirectional isolation material.

[0036] Preferably, the defoaming agent is a polysiloxane defoaming agent.

[0037] Preferably, the leveling agent is a water-based leveling agent BYK-333.

[0038] On the other hand, the present invention also provides a method for preparing a wear-resistant and durable one-way insulation material, comprising the following steps: adding modified nano magnesium silicate, hydrated magnesium silicate and titanium dioxide to the modified acrylate copolymer, mixing, stirring evenly, and then adding a defoaming agent and a leveling agent to obtain the wear-resistant and durable one-way insulation material.

[0039] On the other hand, the present invention also provides an application of a wear-resistant and durable one-way insulation material, which comprises the following steps: adding the one-way insulation material into a foaming machine for foaming, then coating the substrate with a coating machine, and drying after coating.

[0040] In some embodiments of the present invention, the foaming ratio is 3 to 6 times, the coating speed is 10 to 30 m / min, and the coating weight is 50 to 80 g / m 2 .

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The one-way insulation material provided by the present invention is a one-way insulation material that uses acrylic ester polymer as the main film-forming raw material, has excellent wear resistance and durability, and is not prone to damage. The service life of the one-way insulation material is extended, and the one-way insulation material has excellent performance when used in the vacuum infusion molding process of wind turbine blades as a one-way insulation membrane.

[0043] (2) The present invention prepares a medium-soft self-crosslinking acrylic copolymer emulsion, which has improved elasticity and ductility, is not easy to break, and has stronger stability, which improves usability. At a specific monomer copolymerization amount, it avoids the adverse effect on the moisture permeability caused by the condensation of some hydroxyl groups at high temperature to form ether bonds and then forming a film on the surface of the substrate cloth, thereby significantly improving the moisture permeability of the isolation material. The specific selection of dodecafluoroheptyl methacrylate to modify the acrylic copolymer greatly reduces the surface tension of the substrate cloth, and at the same time effectively improves the durability of the substrate cloth. The applicant also adds nano-silicon dioxide to participate in the polymerization of the acrylic copolymer, thereby improving the durability, stability and uniformity of the performance of the copolymer. When it is used as a coating resin film for polyester or nylon substrate cloth, it has good wash fastness and extends the service life of the unidirectional isolation material. On the other hand, the unidirectional isolation material with the modified acrylic copolymer and the composite magnesium silicate filler as the main raw materials can form a continuous microporous structure on the surface of the substrate cloth, exerting good unidirectional isolation performance.

[0044] (3) The present invention modifies the nano magnesium silicate by adding a specific titanate coupling agent and paraffin, thereby increasing the compatibility of the nano magnesium silicate in the system. At the same time, by utilizing its small size and high chemical reactivity, it is deposited on the micro defects on the friction surface of the one-way isolation material, which can better fill the friction interface and improve the wear resistance of the one-way isolation material, thereby increasing the service life; on the other hand, the chemical stability of the modified nano magnesium silicate is improved, and when it is compatible with other components in the system, it can also effectively improve the chemical resistance and scrub resistance of the one-way isolation material; on the other hand, the modified nano magnesium silicate also promotes a certain improvement in the tensile strength of the one-way isolation material. DETAILED DESCRIPTION

[0045] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0046] If not otherwise specified, the reagents used below can be easily obtained from commercial companies, among which nano magnesium silicate was purchased from Lingshou County Shengyun Mineral Products Processing Plant; polysiloxane defoamer was purchased from Jiangsu Hai'an Petrochemical Plant; fatty alcohol polyoxyethylene ether AEO-9 was purchased from Guangzhou Junxin Chemical Technology Co., Ltd.; ethylene-vinyl acetate copolymer was purchased from Suzhou Yitianli Plastic Co., Ltd.

[0047] In the following preparation examples, the titanate coupling agent used is titanate coupling agent LK-201.

[0048] Preparation Example 1

[0049] The preparation steps of modified acrylate copolymer I are as follows:

[0050] (1) adding fatty alcohol polyoxyethylene ether AEO-9 and deionized water into a container to obtain a 20 wt % emulsifier solution;

[0051] (2) Add 0.77 mL of the emulsifier solution obtained in step (1) to the reactor, and then add 0.15 g of dodecafluoroheptyl methacrylate, 0.07 g of nano-silicon dioxide, 2 g of vinyl acetate, 3 g of butyl acrylate, 0.1 g of hydroxyethyl methacrylate and 0.05 g of sodium hydroxide in sequence, disperse by ultrasound for 35 min, heat to 55 ° C, react for 25 min, add 0.02 g of ammonium persulfate, keep warm and react for 35 min, add 0.03 g of ammonium persulfate within 2.5 h, wait for the temperature to drop to 25 ° C after the reaction, and filter to obtain modified polyacrylate copolymer I.

[0052] Preparation Example 2

[0053] The preparation steps of modified acrylate copolymer II are the same as those of Preparation Example 1, except that 1.8 g of butyl acrylate is added.

[0054] Preparation Example 3

[0055] The preparation steps of modified acrylate copolymer III are the same as those of Preparation Example 1, except that 4.2 g of butyl acrylate is added.

[0056] Preparation Example 4

[0057] The preparation steps of modified acrylate copolymer IV are the same as those of Preparation Example 1, except that 0.025 g of dodecafluoroheptyl methacrylate is added.

[0058] Preparation Example 5

[0059] The preparation steps of modified acrylate copolymer V are the same as those of Preparation Example 1, except that 0.275 g of dodecafluoroheptyl methacrylate is added.

[0060] Preparation Example 6

[0061] The preparation steps of modified acrylate copolymer VI are as follows:

[0062] (1) adding fatty alcohol polyoxyethylene ether AEO-9 and deionized water into a container to obtain a 20 wt % emulsifier solution;

[0063] (2) Add 0.77 mL of the emulsifier solution obtained in step (1) into a reactor, and then add 0.15 g of dodecafluoroheptyl methacrylate, 2 g of vinyl acetate, 3 g of butyl acrylate, 0.1 g of hydroxyethyl methacrylate and 0.05 g of sodium hydroxide in sequence, disperse by ultrasound for 35 min, heat to 55° C., react for 25 min, add 0.02 g of ammonium persulfate, keep warm and react for 35 min, add 0.03 g of ammonium persulfate within 2.5 h, wait for the temperature to drop to 25° C. after the reaction is completed, and filter to obtain a modified polyacrylate copolymer VI.

[0064] Preparation Example 7

[0065] The preparation steps of the first modified nano magnesium silicate are as follows:

[0066] 40 g of nano magnesium silicate, 0.9 g of titanate coupling agent and 0.3 g of paraffin were added into the reactor, and the mixture was mixed and stirred at a speed of 2250 r / min for 6 min to obtain the first modified nano magnesium silicate.

[0067] Preparation Example 8

[0068] The preparation steps of the second modified nano magnesium silicate are the same as those of Preparation Example 7, except that 0.05 g of paraffin is added.

[0069] Preparation Example 9

[0070] The preparation steps of the third modified nano magnesium silicate are the same as those of Preparation Example 7, except that 0.6 g of paraffin is added.

[0071] Preparation Example 10

[0072] The preparation steps of the fourth modified nano magnesium silicate are the same as those of Preparation Example 7, except that 1.2 g of titanate coupling agent is used to replace 0.9 g of titanate coupling agent and 0.3 g of paraffin.

[0073] Preparation Example 11

[0074] The preparation steps of the fifth modified nano magnesium silicate are the same as those of Preparation Example 7, except that 1.2 g of paraffin is used to replace 0.9 g of titanate coupling agent and 0.3 g of paraffin.

[0075] Example 1

[0076] A wear-resistant and durable one-way insulating material, the one-way insulating material comprising the following raw materials in parts by weight: 70 parts of modified acrylate copolymer I, 5 parts of first modified nano magnesium silicate, 15 parts of hydrated magnesium silicate, 2 parts of titanium dioxide, 0.03 parts of polysiloxane defoamer and 0.02 parts of BYK-333;

[0077] The preparation method of the wear-resistant and durable one-way insulation material of this embodiment comprises the following steps: adding the first modified nano magnesium silicate, hydrated magnesium silicate and titanium dioxide to the modified acrylate copolymer I, mixing and stirring evenly, and then adding polysiloxane defoamer and BYK-333 to obtain the wear-resistant and durable one-way insulation material.

[0078] Example 2

[0079] A wear-resistant and durable one-way insulating material, the one-way insulating material comprising the following raw materials in parts by weight: 60 parts of modified acrylate copolymer I, 2 parts of first modified nano magnesium silicate, 10 parts of hydrated magnesium silicate, 1 part of titanium dioxide, 0.01 parts of polysiloxane defoamer and 0.01 parts of BYK-333;

[0080] The preparation method of the wear-resistant and durable one-way isolation material in this embodiment is the same as that in Embodiment 1.

[0081] Example 3

[0082] A wear-resistant and durable one-way insulating material, the one-way insulating material comprising the following raw materials in parts by weight: 80 parts of modified acrylate copolymer I, 8 parts of first modified nano magnesium silicate, 20 parts of hydrated magnesium silicate, 3 parts of titanium dioxide, 0.05 parts of polysiloxane defoamer and 0.03 parts of BYK-333;

[0083] The preparation method of the wear-resistant and durable one-way isolation material in this embodiment is the same as that in Embodiment 1.

[0084] Example 4

[0085] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer II is used to replace the modified acrylate copolymer I in equal amounts.

[0086] Example 5

[0087] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer III is used to replace the modified acrylate copolymer I in equal amounts.

[0088] Example 6

[0089] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer IV is used to replace the modified acrylate copolymer I in equal amounts.

[0090] Example 7

[0091] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer V is used to replace the modified acrylate copolymer I in equal amounts.

[0092] Example 8

[0093] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer VI is used to replace the modified acrylate copolymer I in equal amounts.

[0094] Example 9

[0095] A wear-resistant and durable one-way isolation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the first modified nano magnesium silicate is replaced by an equal amount of the second modified nano magnesium silicate.

[0096] Example 10

[0097] A wear-resistant and durable one-way isolation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the first modified nano magnesium silicate is replaced by an equal amount of the third modified nano magnesium silicate.

[0098] Embodiment 11

[0099] A wear-resistant and durable one-way isolation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the first modified nano magnesium silicate is replaced by an equal amount of the fourth modified nano magnesium silicate.

[0100] Example 12

[0101] A wear-resistant and durable one-way isolation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the first modified nano magnesium silicate is replaced by an equal amount of the fifth modified nano magnesium silicate.

[0102] Comparative Example 1

[0103] A wear-resistant and durable one-way insulating material, the one-way insulating material comprising the following raw materials in parts by weight: 70 parts of modified acrylate copolymer I, 20 parts of hydrated magnesium silicate, 2 parts of titanium dioxide, 0.03 parts of polysiloxane defoamer and 0.02 parts of BYK-333;

[0104] The preparation method of the wear-resistant and durable one-way isolation material of this comparative example is the same as that of Example 1.

[0105] Comparative Example 2

[0106] A wear-resistant and durable one-way insulating material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified acrylate copolymer I is replaced by an equal amount of ethylene-vinyl acetate copolymer.

[0107] Performance Testing

[0108] The unidirectional insulating materials obtained in the above-mentioned Examples 1-12 and Comparative Examples 1-2 were added to a foaming machine for foaming, and then coated on a polyester substrate (model WF330, purchased from Leadgo-Tech) by a coating machine. After coating, the samples were dried at 50°C to obtain performance tests; wherein: the foaming ratio was 5 times, the coating speed was 20 m / min, and the coating weight was 65 g / m 2 ; See Table 1 for specific test results:

[0109] (1) Air permeability test: The sample was tested according to the standard GB / T 1038-2000 using a 20 cm 2 The air permeability test is carried out on the area. The greater the gas flow rate, the better the air permeability.

[0110] (2) Abrasion resistance test: The haze of the polyester substrate coated with the unidirectional insulation material was directly tested using a haze meter according to the enterprise standard Q / 6S1204 of the Beijing Institute of Aeronautical Materials (621 Institute). After that, the sample surface was abraded with quartz sand for 200 strokes and then tested again using a haze meter. The difference between the two haze values ​​indicated the abrasion resistance. The smaller the difference, the better the abrasion resistance.

[0111] (3) Tensile performance test: The sample obtained by foaming the unidirectional insulation material was cut into specimens with a size of 164 mm × 10 mm × 4 mm and subjected to a tensile performance test in accordance with standard GB / T1040-2006. The tensile rate was 50 mm / min. The higher the tensile strength, the better the tensile performance.

[0112] Table 1

[0113] project <![CDATA[Gas throughput / × 10 -2 cm 3 / (m 2 ·Pa·d)]]> Wear resistance / % Tensile strength / MPa Example 1 1.32 0.40 36.0 Example 2 1.25 0.44 34.9 Example 3 1.28 0.41 33.1 Example 4 1.15 0.50 32.0 Example 5 1.23 0.53 32.3 Example 6 1.10 0.48 31.5 Example 7 1.03 0.46 29.4 Example 8 1.09 0.73 28.5 Example 9 0.77 1.11 29.6 Example 10 0.80 1.05 30.1 Embodiment 11 0.72 1.25 24.3 Example 12 0.58 1.19 25.0 Comparative Example 1 0.76 1.41 21.9 Comparative Example 2 0.45 1.56 22.5

[0114] As can be seen from Table 1, the unidirectional isolation materials provided by Examples 1 to 3 of the present invention have excellent wear resistance, high tensile strength, and good air permeability;

[0115] In Example 4 and Example 5, the addition amount of vinyl acetate and butyl acrylate was changed, which affected the soft elasticity and ductility of the modified acrylate copolymer, resulting in a decrease in the wear resistance and tensile strength of the unidirectional isolation material;

[0116] The amount of fluorine-containing monomer added was changed in Example 6 and Example 7. In particular, in Example 7, although the wear resistance was good, the tensile properties decreased.

[0117] The modified acrylate copolymer prepared in Example 8 did not contain nano-silicon dioxide, and the ductility of the system was affected, and the tensile strength was significantly reduced;

[0118] In Example 9 and Example 10, the total amount of modifier added in the modified nano magnesium silicate was changed, which was affected by the dispersion amount and agglomeration phenomenon, resulting in a decrease in tensile strength and also having an adverse effect on the air permeability of the system;

[0119] In Example 11 and Example 12, only titanate coupling agent and paraffin were added to modify the nano magnesium silicate, and the prepared modified nano magnesium silicate could not be evenly dispersed in the system, resulting in a decrease in the comprehensive performance of the unidirectional isolation material;

[0120] Comparative Example 1 adds a single hydrated magnesium silicate. Compared with Example 1, it can be seen that the modified nano magnesium silicate prepared specifically in the present invention can play a better role in reinforcing the performance in the system;

[0121] Comparison of Comparative Example 2 with Example 1 shows that replacing the modified acrylate copolymer I with an equal amount of ethylene-vinyl acetate copolymer will lead to a significant decrease in the wear resistance and tensile strength of the unidirectional isolation material.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A wear-resistant and durable one-way isolation material, characterized in that: The one-way insulating material comprises the following raw materials in parts by weight: 60-80 parts of modified acrylate copolymer, 2-8 parts of modified nano magnesium silicate, 10-20 parts of hydrated magnesium silicate, 1-3 parts of titanium dioxide, 0.01-0.05 parts of defoaming agent and 0.01-0.03 parts of leveling agent; Wherein, the viscosity of the modified acrylate copolymer is 1000-2000 mPa·s at 25°C; The preparation steps of the modified acrylate copolymer are as follows: (1) adding an emulsifier and deionized water into a container to obtain an emulsifier solution; (2) Add the emulsifier solution obtained in step (1) into the reactor, then add the fluorine-containing monomer, nano-silica, vinyl acetate, butyl acrylate, hydroxyethyl methacrylate and catalyst in sequence, disperse by ultrasound for 30-40 minutes, heat to 50-60° C., react for 20-30 minutes, add the first part by weight of initiator, keep the temperature to react for 30-40 minutes, add the second part by weight of initiator within 2-3 hours, wait for the temperature to drop to 20-30° C. after the reaction is completed, and filter to obtain the modified polyacrylate; The mass ratio of vinyl acetate to butyl acrylate is 1:(1-2); The amount of the fluorinated monomer added is 1-5% of the total mass of vinyl acetate and butyl acrylate; The preparation steps of the modified nano magnesium silicate are as follows: Adding nano magnesium silicate and a modifier into a reactor, mixing and stirring at a speed of 2000-2500 r / min for 2-10 min, to obtain the modified nano magnesium silicate; The modifier is a mixture of a titanate coupling agent and paraffin; The amount of the modifier added is 1-5% of the mass of the nano magnesium silicate.

2. A method for preparing the wear-resistant and durable one-way isolation material according to claim 1, characterized in that: The method comprises the following steps: adding modified nano magnesium silicate, hydrated magnesium silicate and titanium dioxide into the modified acrylic ester copolymer, mixing and stirring evenly, and then adding a defoamer and a leveling agent to obtain the wear-resistant and durable one-way insulating material.

3. An application of the wear-resistant and durable one-way insulation material according to claim 1 or the wear-resistant and durable one-way insulation material obtained by the preparation method according to claim 2, characterized in that: The application comprises the following steps: adding the one-way insulating material into a foaming machine for foaming, coating the substrate with a coating machine, and drying after coating.

4. The use of a wear-resistant and durable one-way isolation material according to claim 3, characterized in that: The foaming ratio is 3-6 times, the coating speed is 10-30 m / min, and the coating weight is 50-80 g / m 2 .

Citation Information

Patent Citations

  • Breathable isolating membrane

    CN214774512U

  • Preparation method of porous composite isolating membrane

    CN104262674A

  • Enclosure metal surface treatment agent

    CN105968984A